Effects of narcissism, leisure boredom, and gratifications sought on user-generated content among net-generation users - Chi-Him Poona Damon; Wing-Chi Leung Louis (International Telecommunications Society (ITS), 2011)
This research identifies the gratifications sought by the net-generation when producing user-generated content (UGC) on the internet. Members of the Net-generation want to vent negative feelings, show affection to their frieds and relatives, be involved in others' lives, and fulfill their need to be recognized. These gratifications were all found to be significantly associated with the users' various levels of participation in UGC (e.g., Facebook, YouTube, blogs, online forums, etc.) What's more, narcissism was predictive of content generation in social networking sites, blogs, and personal webpage, while leisure boredom was significantly linked to expressing views in forums, updating personal website, and participating in consumer reviews. In particular, the results showed the Net-geners who encountered leisure boredom had a higher tendency to seek interaction with friends online. Implications of findings are discussed.
Keywords: 330; Narcissism; leisure boredom; user-generated content; uses and gratifications